2023
DOI: 10.14309/ajg.0000000000002564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucagon-Like Peptide-1 Receptor Agonists on Bowel Preparation for Colonoscopy

Rebecca Yao,
Khushboo S. Gala,
Wissam Ghusn
et al.

Abstract: Background: Inadequate bowel preparation can result in decreased diagnostic accuracy and therapeutic safety of colonoscopy for colon cancer screening. The Boston Bowel Preparation Scale (BBPS) has been used to assess the quality of bowel preparation. Glucagon-Like Peptide-1 Receptor Agonists (GLP-1RAs) are commonly used medications for diabetes mellitus and obesity that are known to delay gastrointestinal motility. We hypothesized that the use of GLP-1RAs would be associated with decreased quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…According to a retrospective study conducted by Yao et al [ 26 ], 15.5% of patients receiving GLP-1 RA had a Boston Bowel Preparation Scale (BBPS) score of less than 5, compared to 6.6% of patients not receiving GLP-1 RA[ 26 ]. An observational study done by Tong et al [ 27 ] did not notice a significant difference in the incidence of inadequate bowel preparation on colonoscopy in patients taking Liraglutide, Sitagliptin, and patients not on GLP-1 RA.…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective study conducted by Yao et al [ 26 ], 15.5% of patients receiving GLP-1 RA had a Boston Bowel Preparation Scale (BBPS) score of less than 5, compared to 6.6% of patients not receiving GLP-1 RA[ 26 ]. An observational study done by Tong et al [ 27 ] did not notice a significant difference in the incidence of inadequate bowel preparation on colonoscopy in patients taking Liraglutide, Sitagliptin, and patients not on GLP-1 RA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings revealed that the percentage of patients with poor bowel preparation was significantly greater in the GLP-1RA group than in the control group (15.5% vs 6.6%, P = 0.01). Notably, a greater proportion of patients in the GLP-1RA group required a repeat colonoscopy due to poor bowel preparation than did those in the control group (18.9% vs 11.1%, P = 0.041)[ 122 ].…”
Section: Incretin Ras and Perioperative Managementmentioning
confidence: 99%
“…Specifically, the contentious issue of potential pulmonary aspiration associated with GLP-1 agonists during endoscopy as well as proper preparation for colonoscopy has been highlighted. These complications directly affect patients, GI providers, and clinicians providing sedation or anesthesia (26–28) The data are in their early stages but point towards a need to carefully weigh the risks and benefits of these medications around endoscopies. The effectiveness and safety of weight loss treatments in GI and liver diseases has also been explored (29,30).…”
mentioning
confidence: 99%